The Magic of Dukun Jani and the Revival of Neo-Saminism in Sedulur Sikep: Political Economy of Grobogan Farmers Against the Cement Industry - Candraningrum, Dewi (Salasika, 2019)
Maintaining the karst and biodiversity of the North Kendeng Mountains, which extend across five kabupaten in Central Java (Rembang, Blora, Pati, Kudus, and Grobogan) is not an easy task. A PT Semen Indonesia (PT SI) cement factory has been established on Bokong Rembang Mountain, and PT Semen Grobogan (PT SG) was planned to be opened in Kecamatan Tanggungharjo at the end of 2016. According to the Bupati of Grobogan, Sri Sumarni, as quoted by Tribun Jateng on 2 September 2016, “in addition to pressure from the people, the establishment of a cement factory will absorb a lot of local jobs”. She then went on to say that the authority to approve PT SG is not only in the hands of Grobogan Kabupaten Government but also in the hands of the Central Java Provincial Government. “This means that the Kabupaten Government just goes along with the Provincial Government policies and that of Governor Ganjar Pranowo. With the Central Government planning a cement factory moratorium we will get together with the Regional House of Representatives (DPRD) and prominent local figures to discuss the issue.